News: Repealed: What Next? - Lockhart, Katie (Trinity Student Medical Journal, 2018)
Last Tuesday, TCD Obstetrics and Gynaecology Student Society (TOGSS), TCD Undergraduate Society of General Practice and Medical Students for Choice (MSFC) TCD welcomed a variety of prominent healthcare professionals to discuss the future of women’s healthcare in post-repeal Ireland. The societies, in their first ever collaboration, were joined by Dr. Marion Dyer, Dr. Pau Castell Montrull, Dr. Mary Short, Ms. Karen Canning and Senator Catherine Noone, an all-female panel ready to discuss the challenges that will be faced in the coming months as the legislation is passed and the new service rolled out. The evening began as medical students and doctors gathered outside the Durkan theatre of St. James’s Hospital, having their own discussions over wine and cheese, before Brittany Telford, Co-Chair of TOGSS welcomed the audience with a short speech. Claudia O’Driscoll Greaney, Chair of the GP Society, then introduced and invited each panelist in turn to take to the stage and share their differing perspectives on the upcoming changes. In her opening address, Telford reminded the audience what a memorable time in Irish history this is. Following a lengthy campaign, on May 25, 2018 the Irish people voted by 66.4% to remove the eighth amendment of the Constitution of Ireland, which since 1983 has recognized the life of the unborn fetus as equal to that of the mother, thus restricting termination of pregnancy. In September, the Bill to repeal this amendment was signed into law by President Michael D Higgins, meaning the Oireachtas is now free to legislate in regard to the provision of abortion care in Ireland. “I would hope that it would get through before Christmas, but I don’t think we should rush it just to get it done and have a system that isn’t ready,” said Senator Noone, Deputy leader of the Seanad, who played a pivotal role in the referendum and chaired the Committee on the Eighth Amendment. The plan for the new legislation is to allow a GP led abortion service, available for all women up to 12 weeks of pregnancy, and from 12-24 weeks only in certain circumstances. This month, the Select Oireachtas Committee on Health sat to discuss amendments to the legislation, many of which the Senator says she sees as “grounded in distrust of women”. Despite the challenges ahead, she maintained a positive outlook. “The whole process is an excellent example of how deliberative democracy should work,” she said. One of the issues coming up time and time again over the course of the evening was that of resources, in particular the need for ultrasound machines in primary care. “Rapid and easy access to ultrasound is crucial”, said Dr Castell Montrull, a Dublin GP who is a member of GP POCUS (Point of Care Ultrasound). “Why should women in the community get a lesser service than they’re going to get in the hospital? If they need a scan they should get it”, added Dr Mary Short, Director for Women’s Health at the Irish College of General Practitioners (ICGP). Adding to this from the audience at the end of the discussion, Dr Brendan O’Shea, a GP and Professor in Primary Care and Public Health at TCD, put a motion to the floor ‘That this house strongly supports the availability of GP Point of Care Ultrasound as an integral part of providing a safe and convenient service for Women and their partners in this context’. This resulted in a unanimous yes vote and was strongly supported by fellow audience member Dr Tony O’Sullivan, ICGP Special Interest Group Lead for POCUS. The funding for these resources, as well as the need for training of healthcare professionals, are some of the issues that need ironed out before the new legislation can be translated into a functional health care service. Ms. Karen Canning, outgoing Chair at The Irish Practice Nurses Association, highlighted that it is not just doctors affected by the upcoming changes, saying “the training for practice nurses is important, as we may be the first point of contact.” Healthcare professionals with a conscientious objection to abortion are going to be another challenge for the new system to overcome in order to ensure that all women have access to appropriate care within the 12-week time frame allocated in the legislation. This controversial issue caused Dr. Marion Dyer, a Dublin GP and an Associate Professor in the School of Public Health to pose the audience with the question, “is it appropriate for a doctor, if a woman comes in distress, to say not only will I not prescribe, I will not give you any information as to where you can go?” Dr. Short discussed some of the practicalities of the new service that aim to improve functionality and accessibility, saying “we need a 24-hour counselling phone line, and a preliminary triaging system”, also emphasizing the need for a high standard of post-abortion care and provision of contraception. Dr. Dyer, an active member of Doctors for Choice Ireland, was also keen to disparage the notion that the number of Irish women having abortions is going to dramatically increase with the new law, putting it simply as “what is now secret will become visible.” She went on to quote the WHO figure of 94,000 deaths worldwide due to unsafe abortion between 2003 and 2012 and expressed her hope that women would find the new system more accessible than attempting to terminate pregnancy without medical support. Despite her impassioned views, the evening did not descend into the traditional debate on the ethical and moral views on abortion, but rather stayed focused on the logistics of the new service and meeting the needs of women in this new era in Irish healthcare. Ms. Canning left the audience with the fitting sentiment, “we must treat all our patients with dignity and respect, no matter what their issues are.” Speaking afterwards to Allison Clark, secretary of MSFC TCD about the success of the event, she said “It was great to hear what has been done so far since the repeal, where we will be once the law is in place, and what to expect to change in terms of care given as medical professionals.” Telford concurred, saying that “the event was a great success! It was exciting to have such inter-societal collaboration and most importantly, our diverse panelists gave very interesting perspectives on how healthcare may be changing in the future. We are hopeful that this discussion continues the momentum for change.” Photographs courtesy Emily Nguyen